Experiences from the academic training. Study about the identity of the novice teacher, second part. - Rivas-Flores, José Ignacio; Cortés-González, Pablo; Leite-Méndez, Analía Elizabeth (My University, 2015)
We present some progresses of the current research project we are developing called "The professional identity of teacher studies”. It aims to analyse the training received by students in the faculties of education in the Autonomous Community of Andalusia, especially in the degrees of pre-school education and primary education. To that effect we enquiry about the influence of the experience as school student in their training and what kind of professional identity they are generating along the formation period and after five years of activity as teachers. We present some results from the second phase of the research project: The analysis of the teacher students experience accounts in the college
Keywords: Profesores - Formación profesional; Narratives; Teacher Identity; Education; Academic training